2014
DOI: 10.1371/journal.pntd.0002856
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Uptake by Paracoccidioides spp. Is Receptor-Mediated

Abstract: Iron is essential for the proliferation of fungal pathogens during infection. The availability of iron is limited due to its association with host proteins. Fungal pathogens have evolved different mechanisms to acquire iron from host; however, little is known regarding how Paracoccidioides species incorporate and metabolize this ion. In this work, host iron sources that are used by Paracoccidioides spp. were investigated. Robust fungal growth in the presence of the iron-containing molecules hemin and hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 72 publications
1
70
0
Order By: Relevance
“…Other yeasts such as Candida parapsilosis and Paracoccidioides brasiliensis use Rbt5-like proteins to acquire heme (18,19). In the case of Cryptococcus neoformans, the extracellular heme-binding glycoprotein Cig1 is required for exogenous heme uptake (20).…”
mentioning
confidence: 99%
“…Other yeasts such as Candida parapsilosis and Paracoccidioides brasiliensis use Rbt5-like proteins to acquire heme (18,19). In the case of Cryptococcus neoformans, the extracellular heme-binding glycoprotein Cig1 is required for exogenous heme uptake (20).…”
mentioning
confidence: 99%
“…Bailão et al . found the opposite was true for P. brasiliensis Pb18 (S1) and P. lutzii Pb01 and sheep erythrocytes . We believe that these contrasting results may be attributable to differences in our strains of P. lutzii (LDR2) and P. restrepiensis (B339); however, we cannot rule out a possible influence of iron in the culture medium because we did not use a completely iron‐free agar before CFA production.…”
Section: Discussionmentioning
confidence: 84%
“…This study demonstrated the presence of a hemolytic factor on the cell surface and as a secreted component for releasing hemoglobin, as hypothesized by Bailão et al . . The same group demonstrated that this is a possible iron source; they found that there was no upregulation of zrt1 transcript, which encodes for a zinc/iron permease, after incubation of yeasts of P. brasiliensis with human blood, suggesting there is no limit on available iron in this situation .…”
Section: Discussionmentioning
confidence: 97%
“…In another related study, it was also demonstrated that Paracoccidioides may use haemoglobin as an iron source, most probably through receptor‐mediated pathways, since iron‐related genes that encode haemoglobin receptors were identified in the genome of this fungal pathogen. In this study, the authors observed that expression of these related genes, including those encoding for proteins involved in amino acid assembly, as well as nitrogen, sulphur and iron–sulphur metabolism, were induced under low‐inorganic iron conditions or in the presence of haemoglobin (Bailão et al ., ).…”
Section: Metabolic Pathwaysmentioning
confidence: 97%